0719 Understanding Sleep Characteristics in Nursing-Home Eligible Community Dwelling Older Adults: A Mixed Methods Study. (27th April 2018) - McPhillips, M V; Dickson, V V; Cacchione, P Z; Li, J; Gooneratne, N S; Riegel, B J
Abstract: Introduction: More than half of older adults have at least one sleep related complaint and older adults with chronic conditions and functional limitations are even more likely to suffer from sleep disturbances. Sleep disturbances can lead to poor health outcomes; yet little is known about sleep in nursing-home eligible community dwelling older adults. The aim of this study was to describe sleep characteristics in this at-risk population. Methods: We conducted a concurrent nested mixed methods study. A purposive sample of 40 older adults (aged ≥55) was recruited from one urban Program of All-Inclusive Care for Elders. Qualitative data were obtained through in-depth, semi-structured interviews. Objective sleep measures (one-week wrist Actigraphy and sleep diary) and standardized sleep surveys (Pittsburgh Sleep Quality Index [PSQI]; Insomnia Severity Index [ISI]) augmented the qualitative data. Qualitative and quantitative data were collected concurrently, analyzed sequentially, and integrated thereafter. Results: Our final sample (n=40) was primarily female (85%), Black (100%), older adults with a mean age of 72 ± 9.5 years. Only 12.5% of participants got the recommended (420–480 min or 7–8 hours) sleep at night (393.59 ± 78.33 min); 75% did not get enough sleep and 12.5% got too much sleep. About 25% had long sleep latency (23.22 ± 18.45 min); almost all had long periods of wakefulness after sleep onset (107.93 ± 50.1 min) and 87.5% had poor sleep efficiency (72.98% ± 9.30%). The majority (70%) of the participants had poor sleep quality (PSQI scores 9.25 ± 5.07); more than half of the participants reported insomnia symptoms (ISI scores 9.23 ± 7.17). Regardless of whether a participant identified as a good or poor sleeper, few had concerns about their sleep. These older adults had adjusted their health expectations and adapted to sleep disturbances. Conclusion: Nocturnal sleep disturbances were common in these at-risk older adults; yet they did not perceive them as problematic. Given the poor outcomes associated with sleep problems, clinicians must proactively assess sleep. Support (If Any): T32NR009356, T32HL07953, Frank Morgan Jones, Tyson, and Sigma Theta Tau Funding.